Longitudinal evaluation of local muscle conditions in a rat model of gastrocnemius muscle injury using an in vivo imaging system. Issue 7 (10th April 2015) - Inage, Kazuhide; Sakuma, Yoshihiro; Yamauchi, Kazuyo; Suganami, Akiko; Orita, Sumihisa; Kubota, Go; Oikawa, Yasuhiro; Sainoh, Takeshi; Sato, Jun; Fujimoto, Kazuki; Shiga, Yasuhiro; Takahashi, Kazuhisa; et al.
ABSTRACT This study aimed to evaluate the time course of local changes during the acute phase of gastrocnemius muscle strain, in a rat model, using an in vivo imaging system. Thirty‐eight, 8‐week‐old Sprague‐Dawley male rats were used in our study. Experimental injury of the right gastrocnemius muscle was achieved using the drop‐mass method. After inducing muscle injury, a liposomally formulated indocyanine green derivative (LP‐iDOPE, 7 mg/kg) was injected intraperitoneally. We evaluated the muscle injuries using in vivo imaging, histological examinations, and enzyme‐linked immunosorbent assays. The fluorescence peaked approximately 18 h after the injury, and decreased thereafter. Histological examinations revealed that repair of the injured tissue occurred between 18 and 24 h after injury. Quantitative analyses for various cytokines demonstrated significant elevations of interleukin‐6 and tumor necrosis factor‐α at 3 and 18 h post‐injury, respectively. The time course of fluorescence intensity, measured using in vivo imaging, demonstrated that the changes in cytokine levels and histopathologic characteristics were consistent. Specifically, these changes reached peaked 18 h post‐injury, followed by trends toward recovery. © 2015 Orthopaedic Research Society. Published by Wiley Periodicals, Inc. J Orthop Res 33:1034–1038, 2015.